Enhancing capacity for african agricultural research: selected models and lessons - Babu, Suresh Chandra; Annor-Frempong, Ireme; Asenso-Okyere, Kwadwo (International Food Policy Research Institute, 2011)
This paper presents a review of three existing models of capacity building to provide an understanding of strategies and approaches that have been successful in strengthening human and institutional capacity for agricultural research in Africa. The paper documents lessons in capacity strengthening from these models that can be scaled up and out to other contexts. While the three programs reviewed emphasize building capacities by developing local institutions, a major challenge is the programs' sustainability because they continue to depend on external sources of funding. In order to take advantage of the emerging global interest in capacity strengthening, it is argued that national agricultural research systems need to prepare by identifying their strategic capacity and institutional strengthening needs, as well as providing overall leadership to enable the successful use of the capacities developed. While further innovations are needed to strengthen capacities cost-effectively, the three programs reviewed highlight the role of national leadership in absorbing the capacity created, thereby emphasizing the importance of an enabling environment that can maximize the benefits of the capacities strengthened. Unless the skills developed through these programs are complemented by effective organizational capacity, providing the motivation and incentives needed to put the newly created skills to effective use, these capacities may well be eroded.